2019
DOI: 10.1007/s00508-019-1462-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnose und Management der Osteoporose bei Diabetes mellitus (Update 2019)

Abstract: Zusammenfassung Diabetes mellitus und Osteoporose zählen zu den häufigsten chronischen Erkrankungen und kommen deshalb beide häufig in ein und demselben Individuum vor. Da die Prävalenz beider mit steigendem Alter zunimmt, wird in Anbetracht der Altersstruktur unserer Bevölkerung deren Häufigkeit zunehmen. Patienten mit Diabetes haben ein erhöhtes Risiko für Fragilitätsfrakturen. Die Pathophysiologie ist unklar und vermutlich multifaktoriell. Longitudinale Studien haben den Nachweis erbracht, dass das Fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A subsequent retrospective study in a Canadian cohort (82,094 diabetic adults and 236,682 controls) showed that in subjects with T2D for more than 5 years, there was an increased risk of both fracture at all osteoporotic sites (1.15–95% CIs, 1.09–1.22) and hip fractures (1.4–95% CIs, 1.28–1.53) as compared to T2D patients with a shorter duration of disease [ 135 ]. Based on these data and on other similar observations, a T2D duration of 5 [ 131 , 132 ] or 10 years [ 2 ] was suggested in the position statements. In this respect, however, it should be remarked that T2D often remains a misdiagnosed disease for several years.…”
Section: Assessment Of Fracture Risk In Patients With Type 2 Diabetesmentioning
confidence: 72%
See 2 more Smart Citations
“…A subsequent retrospective study in a Canadian cohort (82,094 diabetic adults and 236,682 controls) showed that in subjects with T2D for more than 5 years, there was an increased risk of both fracture at all osteoporotic sites (1.15–95% CIs, 1.09–1.22) and hip fractures (1.4–95% CIs, 1.28–1.53) as compared to T2D patients with a shorter duration of disease [ 135 ]. Based on these data and on other similar observations, a T2D duration of 5 [ 131 , 132 ] or 10 years [ 2 ] was suggested in the position statements. In this respect, however, it should be remarked that T2D often remains a misdiagnosed disease for several years.…”
Section: Assessment Of Fracture Risk In Patients With Type 2 Diabetesmentioning
confidence: 72%
“…In fact, the measurement of BMD or the use of algorithms such as FRAX often underestimates fracture risk in patients with T2D [ 15 , 16 ]. Thus, the presence of a previous fragility fracture, together with specific risk factors associated with increased fracture risk in T2D, represents the initial information to be considered for the stratification of fracture risk in these patients, as recently outlined by some position statements [ 2 , 131 , 132 ]. A representative flowchart summarizing the outcomes from one of these documents [ 2 ] that is also, in part, consistent with a previous report from a working group from the International Osteoporosis Foundation [ 131 ] is shown in Figure 3 .…”
Section: Assessment Of Fracture Risk In Patients With Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as IA prevent peripheral estrogen production, they suppress circulating estrogen levels, causing accelerated bone loss and an increased risk of fractures (YAO et al, 2020). Furthermore, DM2 is another one of the many chronic conditions associated with the development of osteoporosis (MUSCHITZ et al, 2019). In this context, patients at increased risk of bone loss should undergo bone densitometry (BMD) within 3 months after AI therapy accompanied by supplementation and preventive therapy to prevent bone loss (OTTANELLI, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…According to the International Osteoporosis Foundation (IOF), diabetes and bone workout group, T-score ≤ -2 and not -2.5 is a strong indication of osteoporosis treatment administration [40]. DEXA should be accompanied by TBS measurement while the FRAX score should be adjusted for T2DM [40][41]. This should be done by clicking the choice of secondary osteoporosis in the FRAX tool.…”
Section: Discussionmentioning
confidence: 99%